Assessment of Articular Cartilage by Second Harmonic Microscopy: Challenges and Opportunities - Kumar, Rajesh; Kumar, Anup (Frontiers in Physics, 2019)
Second harmonic microscopy (SHM) has emerged as a powerful nondestructive optical imaging modality that has high potential to perform the advanced structural characterization of intact articular cartilage. This article provides the current status, opportunities and challenges of SHM for the use in cartilage evaluation. A novel perspective on SHM is being addressed that includes the reason, need and the importance of SHM in the assessment of articular cartilage. By taking the advantage of collagen specificity and high-resolution imaging, SHM can detect the structural and morphological changes in early stage cartilage damage that would otherwise be overlooked by standard clinical imaging methods such as radiography and arthroscopy. The current status of SHM for articular cartilage analysis and the major progress reported in recent literature are briefly described herein. We summarize the status of scientific efforts and the challenges that need to overcome before moving towards clinical applications of SHM in the context of cartilage evaluation.